2022
DOI: 10.1186/s40659-022-00409-y
|View full text |Cite
|
Sign up to set email alerts
|

Sperm DNA integrity does play a crucial role for embryo development after ICSI, notably when good-quality oocytes from young donors are used

Abstract: Based on the inconsistent literature published thus far involving infertile patients, whether intracytoplasmic sperm injection (ICSI) allows overcoming total fertilization failure due to sperm DNA fragmentation is still unclear. Related to this, female factors, which may have a significant impact on assisted reproduction outcomes, can mask male infertility. In this scenario, evaluating ICSI outcomes following cycles using healthy donor gametes could shed light on this realm, as it would avoid the influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…Esbert et al [60] stated that high sperm DNA fragmentation can lead to a delay in early embryo kinetics, which is related to the increase in the time required before the first cell division to activate DNA repair mechanisms in oocyte. Also, Ribas-Maynou et al [61] observed that the overall DNA damage in sperm was associated with a delay in tPNa, tPNf, and t2 which led to an increase in the time of transition from eight cells to the morula stage.…”
Section: Discussionmentioning
confidence: 98%
“…Esbert et al [60] stated that high sperm DNA fragmentation can lead to a delay in early embryo kinetics, which is related to the increase in the time required before the first cell division to activate DNA repair mechanisms in oocyte. Also, Ribas-Maynou et al [61] observed that the overall DNA damage in sperm was associated with a delay in tPNa, tPNf, and t2 which led to an increase in the time of transition from eight cells to the morula stage.…”
Section: Discussionmentioning
confidence: 98%
“…However, the paternal genome also affects the developmental speed of the embryo. As stated in a recent study, poor DNA integrity in sperm can cause delayed embryo development, which may be related to the extended time required for oocytes to repair paternal genetic material ( 33 ). Furthermore, from a more microscopic perspective of molecular biology, after the maternal genome controls are transformed during the 8-16 cell stage of human embryos, transcriptional activation of the paternal genome begins to participate in regulating the process of embryonic development ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a significant portion of the resulting embryos may become arrested in G2/M-stage transition. The cause is the high proportion of aneuploidy of mitotic origin and subsequent disorders in chromosome segregation, resulting in 20 to 30 percent of blastocysts having the so-called mosaic phenotype [ 54 , 55 , 56 ]. Considering these facts and the still incomplete knowledge about the effectiveness or activity and control points of the cell cycle in maturing oocytes as well as in very early embryos, further research in this area is important, but it must be in connection with exogenous environmental factors that have the potential to damage DNA.…”
Section: Cell Cycle Checkpointsmentioning
confidence: 99%